2019
DOI: 10.1192/bja.2019.13
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation and recovery for ethnic minority patients with severe mental illness

Abstract: SUMMARYThere is growing evidence to support recovery and rehabilitation services and interventions for people with severe mental illness (SMI). However, those from ethnic minority communities face inequitable outcomes and access to mental health services and poorer functional outcomes. This article reviews the evidence and discusses facilitators and barriers in the recovery journey of people with SMI from ethnic minority groups. Although there is limited evidence for specific interventions for ethnic minority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…It is entirely likely that different forms of social capital may impact the risk of developing a psychotic disorder in different ways, considering the differential impact of different forms of social capital on symptoms of psychosis in a non-clinical sample (Freeman et al, 2011 ). Once the relationship between specific forms of social capital and risk is further clarified, it may be important to study how specific forms of social capital may impact clinical care and service use (Heslin et al, 2018 ) as well as different forms of recovery (Rotenberg, 2019 ) in diverse clinical populations.…”
Section: Discussionmentioning
confidence: 99%
“…It is entirely likely that different forms of social capital may impact the risk of developing a psychotic disorder in different ways, considering the differential impact of different forms of social capital on symptoms of psychosis in a non-clinical sample (Freeman et al, 2011 ). Once the relationship between specific forms of social capital and risk is further clarified, it may be important to study how specific forms of social capital may impact clinical care and service use (Heslin et al, 2018 ) as well as different forms of recovery (Rotenberg, 2019 ) in diverse clinical populations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Delman and Adams (2022) reported that “in treatment settings, some respondents felt clinicians disregarded their (Black young adults’) reports of medication side effects, and on the whole did not take their treatment perspectives seriously” (p. 6). These mistreatments highlight the importance of training behavioral health researchers and practitioners to understand and recognize cultural differences to better support and improve diverse clients’ psychological and psychosocial recovery from mental illness (Rotenberg, 2019; Whitley & Lawson, 2010).…”
mentioning
confidence: 99%